Accounting Treatment Of Fixed Assets At The Bogor City Housing And Settlement Office In 2021 Based On PSAP No. 07 - Nugraha, Agung Tri; Susanto, Heri (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to analyze compability accounting treatment of fixed assets in Dinas Perumahan dan Permukiman Kota Bogor based on PSAP number 07 2010 about fixed assets. The variables on this study is accounting treatment of fixed assets Dinas Perumahan dan Permukiman Kota Bogor period 2021 and PSAP 07 2010, the result of this study are there is a non compability accounting treatment of fixed assets Dinas Perumahan dan Permukiman Kota Bogor based on PSAP 07 2010, the effect is there is some fixed assets that out of useful year but still recorded in fixed assets.